Canopy development and yield performance of spring wheat under long-term tillage systems: implications for sustainable crop management - Michalska-Klimczak, Beata; Kamińska-Stępień, Sonia; Pacuta, Vladimir; Rašovský, Marek; Wyszyński, Zdzisław (Journal of Water and Land Development, 2026)
Understanding how tillage practices influence canopy development in spring wheat (Triticum aestivum L.) is essential for improving productivity in sustainable farming systems, particularly in temperate regions with variable spring moisture. This study assessed the effects of conventional tillage (CT), reduced tillage (RT), and no-tillage (NT) on spring wheat canopy structure and architecture and examined their relationships with yield formation. A three- season field experiment was conducted on Luvisol soils in central Poland within a four-course crop rotation. Canopy traits, including plant and shoot density, the share of productive shoots, shoot-type distribution, shoot length, spike morphology, and grain parameters, were measured at key growth stages. CT improved stand establishment, tillering capacity, and spike productivity, producing the highest grain yield in all seasons. By contrast, NT reduced the proportion of multi-shoot and fertile plants, shortened spikes, and reduced grain weight, resulting in a yield decline of more than 30% relative to CT. Strong correlations were observed between canopy structure and grain yield and between architectural traits and spike performance. These findings indicate that tillage systems should be evaluated not only in terms of soil-related benefits but also according to their ability to support canopy functionality and yield resilience under increasingly variable climatic conditions.